2000
DOI: 10.1136/gut.47.4.575
|View full text |Cite
|
Sign up to set email alerts
|

HFE gene mutation (C282Y) and phenotypic expression among a hospitalised population in a high prevalence area of haemochromatosis

Abstract: Background-PreviousResults-Fourteen of the 1900 Caucasian subjects (0.74%) were homozygous and 224 (11.8%) were heterozygous for the C282Y mutation, including 32 subjects (1.7%) who were compound heterozygous for the C282Y and H63D mutations. Ten of 14 (71%) homozygous patients displayed mild to moderate biochemical expression of haemochromatosis with a serum ferritin level <550 µg/l, two (14%) patients were "non expressing", and two of five in whom liver biopsies were carried out had cirrhosis, including one … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
19
0
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(24 citation statements)
references
References 31 publications
4
19
0
1
Order By: Relevance
“…Indeed, it is tempting to speculate that overweight-related chronic inflammatory state [9] could allow for an increased production of IL-6 which, in turn, could upregulate the hepcidin gene and result in compensating, at least partly, the defect of hepcidin synthesis due to the HFE mutation [10][11][12]. This hypothesis fits with the report of [13]. It is also in agreement with the demonstration of normal TS levels in most subjects presenting with the insulin resistance associated hepatic iron overload syndrome [14,15].…”
Section: Discussionsupporting
confidence: 77%
“…Indeed, it is tempting to speculate that overweight-related chronic inflammatory state [9] could allow for an increased production of IL-6 which, in turn, could upregulate the hepcidin gene and result in compensating, at least partly, the defect of hepcidin synthesis due to the HFE mutation [10][11][12]. This hypothesis fits with the report of [13]. It is also in agreement with the demonstration of normal TS levels in most subjects presenting with the insulin resistance associated hepatic iron overload syndrome [14,15].…”
Section: Discussionsupporting
confidence: 77%
“…The second step consists of assessing transferrin saturation knowing that (i) normal transferrin saturation allows to rule out haemochromatosis except in case of coexistent inflammatory syndrome [73] or obesity [58], and (ii) increased transferrin saturation is not specific of haemochromatosis, but can be related to laboratory error -which implies having a confirmation of the test at least once -, to excessive iron release from damaged cells (i.e. hepatitis, haemolysis.…”
Section: Diagnosismentioning
confidence: 99%
“…Serum ferritin levels may not always found to be high in C282Y homozygous individuals. A decrease in the value of serum ferritin levels in acute illnesses, even in individuals homozygous for C282Y has been observed (29). Four recent studies of HH, it was detected that in C282Y homozygous individuals normal ferritin levels rates between all homozygotes were found as 25%, 40%, 50% and 80% respectively.…”
Section: Discussionmentioning
confidence: 97%
“…In Northern Europe the majority of the patients with the diagnosis of HH, have this genotype (2,29,(35)(36)(37). However in Central Antolia, screening studies conducted in Istanbul, Ankara and Izmir have reported that the homozygous C282Y gene mutation is absent (8-10, 38, 39).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation